Recovery from stolbur disease in grapevine involves changes in sugar transport and metabolism - Santi, Simonetta; De Marco, Federica; Polizzotto, Rachele; Grisan, Simone; Musetti, Rita (Frontiers in Plant Science, 2013)
Grapevine can be severely affected by phytoplasmas, which are phytopathogenic Mollicutes invading the sieve elements of the host plant. The biochemical and molecular relationships between phytoplasmas and their hosts remain largely unexplored. Equally unknown is an interesting aspect of the pathogen-plant interaction called 'recovery', which is a spontaneous remission of symptoms in previously symptomatic plants. Recovered plants develop resistance mechanisms correlated with ultrastructural and biochemical changes in the sieve elements. Callose as well as sugars are involved in several plant defense processes and signaling. In the present work we have examined the possible involvement of callose, as well as callose synthase, sugar transporter, and cell wall invertase genes, during the infection and after ‘recovery’ of grapevine from Bois Noir (BN). Ultrastructural investigation of leaf tissue showed that callose accumulated in the sieve elements of diseased grapevine; moreover, two genes encoding for callose synthase were up-regulated in the infected leaves. Regarding sucrose, expression analysis showed that sucrose transport and cleavage were severely affected by BN phytoplasma, which induced the establishment of a carbohydrate sink in the source leaf, and was analogous to other obligate biotrophs that acquire most of their nutrients from the host plant. Interestingly, whereas in recovered plants the transcript level of sucrose synthase was similar to healthy plants, sucrose transporters as well as cell wall invertase were expressed to a greater degree in recovered leaves than in healthy ones. Recovered plants seem to acquire structural and molecular changes leading to increases in sucrose transport ability and defense signaling.